Readers Recruit Executive Functions to Self-Correct Miscues during Oral Reading Fluency. (1st November 2020) - Nguyen, Tin Q; Del Tufo, Stephanie N; Cutting, Laurie E.
ABSTRACT: Reading fluency undoubtedly underlies reading competence; yet, the role of executive functions (EFs) is less well understood. Here, we investigated the relation between children's reading fluency and EF. Children's ( n = 82) reading and language performance was determined by standardized assessments and EF by parental questionnaire. Results revealed that the production of more miscues was explained by poorer reading and language performance and EF. Yet, self-correcting a miscue was predicted by better EF, beyond reading and language abilities. Intriguingly, EF partially mediated the relation between reading and self-correction, suggesting that self-correction reflects parallel recruitment and coordination of domain-specific and domain-general processes.